A imprensa na construção da imagem pública do candidato Affonso Penna na eleição de 1906 - Ramos, Thailissa Leticia Andara (2009)
This paper aims to analyze the period of electoral propaganda to the presidency of the Republic of 1906, focusing its object on the only candidate for president, the miner, Affonso Penna. In this sense, we seek to specifically work the role of the press in the candidacy and construction of the public image, from August 1905 to February 1906, in two Rio newspapers: Correio da Manhã and O Paíz newspaper. Among them, the mention of Penna can only be analyzed in the Correio da Manhã Mining Letters, which presents 37% of contents about the candidate. Of these, 54.5% relate to their imagery characterizations and the 45.5% to their candidacy. As for the construction of the theoretical stage refers to the works that include the universe of communication, political and ideological propaganda, especially from the Brazilian perspective. It also seeks to describe the political trajectory of Affonso Penna, against the background of the political environment. As data collection method, we cite the bibliographic and documentary research and as an investigation instrument the content analysis. (AU)